Differences in match running performance of elite male football players relative to playing position - Borko Katanic; Radivoje Radakovic; Stefan Djordjevic; Karuppasamy Govindasamy; Vlad Adrian Geantă; Alexandru Ioan Băltean; Mima Stankovic (Journal of Men's Health)
Background: This study aimed to examine differences in match running performance (MRP) of elite male football players according to their team positions. Methods: The sample included 108 male football players from five Union of European Football Associations (UEFA) Europa League group-stage matches (2021/22). Players’ movement performance was classified by position: central backs (CB; n = 22), fullbacks (FB; n = 21), central midfielders (CM; n = 28), wingers (W; n = 18), forwards (F; n = 19). Movement performance was assessed using the InStat Fitness optical system and classified by velocity: walking, jogging, running, high-intensity running and sprinting. Additional parameters included: total distance, average and maximum movement velocity, and the number of accelerations and sprints performed. Results: The main findings were: (i) Forwards covered a shorter distance (8449 m; p = 0.001) than other players—1587 m less than fullbacks, 1871 m less than central midfielders and 2157 m less than wingers. They also covered less distance in walking (p = 0.006) and jogging (p = 0.001) than other players; (ii) Wingers and central midfielders covered greater distances (p = 0.001) than central backs and forwards; (iii) Central backs covered less distance in high-velocity running (539 m; p = 0.001)—286 m less than fullbacks, 301 m less than central midfielders, 300 m less than wingers and 158 m less than forwards. They also sprinted less (62 m; p = 0.001)—91 m less than fullbacks, 95 m less than wingers and 80 m less than forwards—and performed fewer sprints overall; (iv) Central midfielders and wingers had the highest average velocity (p = 0.001); (v) No differences were found in the number of accelerations or maximum velocity. Conclusions: These findings highlight the different physical demands and roles of various positions in male football, informing training adjustments to enhance players’ abilities.